(untitled) (Research, Society and Development, 2022)
Among the small fruits, the strawberry is the most commercialized pseudofruit in the world. Each year, Brazil has been increasing its production, but it is dependent on cultivars developed by foreign breeding programs. The objective of this work was to evaluate three strawberry accessions developed by a rural producer, in the edaphoclimatic conditions of southern Minas Gerais, analyzing their agronomic potential. Early and total production, number of fruits, diameter (mm), length (mm), weight (g), total soluble solids content (°Brix) was evaluated. It is concluded that the agronomic potential of the accessions NP9 and NP15 are equivalent and in some characteristics superior to the cultivar ’Oso Grande’, and can be recommended for planting in the conditions of southern Minas Gerais, after its registration with MAPA, reducing dependence on cultivars of foreign origin and their implications.